2008
DOI: 10.1097/mao.0b013e31816c7c9e
|View full text |Cite
|
Sign up to set email alerts
|

Sensorineural Hearing Loss After Radiotherapy for Head and Neck Tumors

Abstract: The results of the present study show that DPOAE measurement is a reliable method for determining which patients are at risk of developing SNHL in the early post-RT period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…The incidence of SNHL observed at frequencies above 4 kHz is greater than that observed at frequencies in the speech range (Figure ). The incidence of SNHL reported for the speech frequencies (< 4 kHz) varied from 0% to 85%, whereas 7 studies reported the incidence of high frequency SNHL (≥4 kHz) ranging from 27% to 95% (Table ) . When taking into consideration the reported incidences of all studies, it is noticed that at the shortest follow‐up period, greater SNHL is detected at frequencies above 4 kHz (Figure A); a trend observed up to the maximal mean follow‐up period of 8 years.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The incidence of SNHL observed at frequencies above 4 kHz is greater than that observed at frequencies in the speech range (Figure ). The incidence of SNHL reported for the speech frequencies (< 4 kHz) varied from 0% to 85%, whereas 7 studies reported the incidence of high frequency SNHL (≥4 kHz) ranging from 27% to 95% (Table ) . When taking into consideration the reported incidences of all studies, it is noticed that at the shortest follow‐up period, greater SNHL is detected at frequencies above 4 kHz (Figure A); a trend observed up to the maximal mean follow‐up period of 8 years.…”
Section: Resultsmentioning
confidence: 94%
“…Fourteen research publications were included in the systematic review. Eight were prospective studies and 6 were retrospective studies . All of the publications were observational studies with a level of evidence IV, with the exception of 1 prospective cohort study (IIb).…”
Section: Resultsmentioning
confidence: 99%
“…Yilmaz et al prospectively studied 19 patients with HNSCC treated with RT (mean cochlear dose 90% of 60–70 Gy). Compared with pretreatment audiological tests, none of the patients had SNHL 1 month after RT.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 21 studies included in this review, only 1 study mentioned the use of otoacoustic emissions. In the study by Yilmaz et al, both pure tone audiometry and distortion product‐otoacoustic emissions were measured before, 1 month after, and 12 months after treatment. One month after treatment, none of the patients had a change >10 dB at any frequency based on audiometry.…”
Section: Discussionmentioning
confidence: 99%
“…SNHL occurs in 24% to 67% of patients with head and neck cancer who receive radiation therapy and can develop as early as 6 weeks after the completion of therapy . Transient fluctuations in hearing loss can occur, with more permanent losses becoming clinically apparent at 6 months.…”
Section: Clinical Manifestations Of Radiation Injurymentioning
confidence: 99%